Modulatory Role of Reactive Oxygen Species in Root Development in Model Plant of Arabidopsis thaliana - Zhou, Xuemei; Xiang, Yu; Li, Chenglong; Yu, Guanghui (Frontiers in Plant Science, 2020)
Reactive oxygen species (ROS), a type of oxygen monoelectronic reduction product, have a higher chemical activity than O2. Although ROS pose potential health risks via oxidative stress, mounting evidence suggests that ROS are essential for root and root-hair development in Arabidopsis thaliana. In the present review, we provide an updated perspective on the latest research progress pertaining to ROS in the precise regulation of root-stem-cell maintenance and differentiation, redox regulation of the cell cycle, and root-hair initiation during root growth. Among the different types of ROS, O2•− and H2O2 have been extensively investigated, and they exhibit different gradient distributions in the roots. The concentration of O2•− decreases along a gradient from the meristem to the transition zone and the concentration of H2O2 decreases along a gradient from the differentiation zone to the elongation zone. These gradients are regulated by peroxidases, which are modulated by the UPBEAT1 (UBP1) factor. In addition, multiple transcriptional factors, such as APP1, ABO8, PHB3, and RITF1, which are involved in the brassinolide signaling pathway, converge as an ROS signal to regulate root stem cell maintenance. Furthermore, superoxide anions (O2•−) are generated from the oxidation of mitochondria, ROS produced during plasmid metabolism, H2O2 produced in apoplasts, and catalysis of respiratory burst oxidase homolog (RBOH) in the cell membrane. These ROS can act as a signal to regulate redox status, which regulates the expression of the cell-cycle components CYC2;3, CYCB1;1, and retinoblastoma-related protein, thereby controlling the cell-cycle progression. In the root maturation zone, the epidermal cells located in the H cell position emerge to form hair cells, and plant hormones such as auxin and ethylene regulate root-hair formation via ROS. Furthermore, ROS accumulation can influence hormone signal transduction, and vice versa. Data about the association between nutrient stress and ROS signals in root-hair development are scarce. However, the fact that ROBHC/RHD2 or RHD6 is specifically expressed in root-hair cells and induced by nutrients may explain the relationship. Future studies should focus on the regulatory mechanisms underlying root-hair development, via the interactions of ROS with hormone signals and nutrient components.